Estudo do equilíbrio de adsorção de siloxanos em materiais porosos - Silva, Edilton Nunes da (2020)
Biogas presents itself as a viable option for energy and heat production and it can be produced from several sources, highlighting: waste from food industry, landfills, and sewage. When biogas’ source is sewage, it commonly generates problems in combustion engines due to siloxanes’ presence, mainly octamethylcyclotetrasiloxane (D4) and decamethylcyclopentasiloxane (D5). After combustion of these compounds, there is formation of silicon dioxide that is deposited inside the engine, leading to an increase in expenses with maintenance and interruptions in service. The most used technology for removing siloxanes from biogas is non-regenerative adsorption. Therefore, the use of low cost and easily obtainable materials is essential. In this context, this study evaluated a simple implementation method (liquid phase), as an approximation of real case in a gaseous medium, for prospecting adsorbents that remove siloxanes from biogas. The materials chosen for initial tests were adsorbents normally used in industry (activated carbons, zeolite, and silica gel), in addition to low-cost and easy-to-obtain materials (natural clays) and materials synthesized from waste such as PET and sewage sand. Among these materials, the ones that obtained the best results in initial tests were inorganic adsorbents: blue silica gel, white silica gel, red bauxite, and sand silica, which were characterized by X-ray fluorescence (FRX) and N2 adsorption/ desorption isotherms at 77 K. Textural characterization revealed presence of micropores and narrow mesopores in a range of 10 to 50 Å in the silica gels and mesopores in the bauxite sample, whereas the sand silica showed a wide pore size distribution. The FRX analysis showed a high silicon content in all samples, except for bauxite, which has a high iron and aluminum content. The kinetics of adsorption for the two siloxanes was similar, equilibrium time varied from 25 hours for sand silica, to 150 hours for bauxite. White silica showed the best adsorption results for siloxanes, 66 mg/g for octamethylcyclotetrasiloxane (D4) and 59 mg/g for decamethylcyclopentasiloxane (D5), followed by sand synthesized silica with adsorption capacities of 44 and 58 mg/g for D4 and D5, respectively. In low concentration regions (<300mg/L) the sand silica had a greater adsorption capacity than all other materials studied. Although siloxane isotherms in liquid phase (in nonpolar solvent) do not represent real process conditions, this work has shown that they may be a screening tool for potential adsorbents. Promising materials should be further investigated with real biogas.